Evaluating the dual role of sea water and metakaolin in the performance, efflorescence mitigation, and phase composition of sodium silicate-activated marble powder - Amira A. Shereiqi; Khalifa Al-Jabri; Mohammed S. Meddah; Kazi Md Abu Sohel; Alaa A. Saleh; Hamdy A. Abdel-Gawwad (Developments in the Built Environment)
Marble waste (MW) poses a significant environmental challenge due to its large quantities and difficulty in disposal. This study explored the full utilization of MW powder in creating binder. Combining MW with sodium silicate (Na2SiO3) results in the formation of calcium silicate hydrate (C-S-H) and pirssonite. The resulting binder demonstrated a compressive strength of 15–25 MPa after 28 days of air curing. Using metakaolin provides the system with dissolved aluminosilicate, which mitigates efflorescence through a neutralization process and enhances the compressive strength of the resulting hardened binder. Seawater also proved effective in reducing efflorescence by decreasing the solubility of pirssonite. Moreover, mixing seawater with Na2SiO3 induced the formation of nanoprecipitates, which positively affects the mechanical performance of the resultant binder. For sustainable building practices, using seawater as a mixing water for unreinforced building products is recommended. This conserves freshwater, making it available for other critical applications.